Coronavirus RNA-dependent RNA polymerase interacts with the p50 regulatory subunit of host DNA polymerase delta and plays a synergistic role with RNA helicase in the induction of DNA damage response and cell cycle arrest in the S phase. Issue 1 (31st December 2023) - Quan, Li; Sun, Xinxin; Xu, Linghui; Chen, Rui Ai; Liu, Ding Xiang
ABSTRACT: Disruption of the cell cycle is a common strategy shared by many viruses to create a conducible cellular microenvironment for their efficient replication. We have previously shown that infection of cells with gammacoronavirus infectious bronchitis virus (IBV) activated the theataxia-telangiectasia mutated (ATM) Rad3-related (ATR)/checkpoint kinase 1 (Chk1) pathway and induced cell cycle arrest in S and G2/M phases, partially through the interaction of nonstructural protein 13 (nsp13) with the p125 catalytic subunit of DNA polymerase delta (pol δ). In this study, we show, by GST pulldown, co-immunoprecipitation and immunofluorescent staining, that IBV nsp12 directly interacts with the p50 regulatory subunit of pol δ in vitro and in cells overexpressing the two proteins as well as in cells infected with a recombinant IBV harbouring an HA-tagged nsp12. Furthermore, nsp12 from severe acute respiratory syndrome coronavirus (SARS-CoV) and SARS-CoV-2 was also able to interact with p50. These interactions play a synergistic role with nsp13 in the induction of S phase arrest. The fact that subunits of an essential cellular DNA replication machinery physically associate with two core replication enzymes from three different coronaviruses highlights the importance of these associations in coronavirus replication and virus-host interaction, and reveals the potential of targeting these subunits for antiviral intervention.